Lived experience of teachers in the MTB-MLE as transit curriculum to ESL - Capilastique, Ludy John B
The MTB-MLE as a transitional curriculum from first language to the English language was implemented in the Philippines as a response to the call of UNESCO in providing quality education for all children in the country. In the MTB-MLE, the formal instruction began in the mother tongue with an integration of the local culture, knowledge, and concepts. As the children developed their knowledge in their mother tonguethey created transition from the first language to a second language because according to the language Interdependence Theory, the well=developed mother tongue within the children strengthened the learning of the English language. The MTB-MLE components-first language instruction, cultural integration, and transition to ESL learning-have been the devotion of the policy makers andeducational researchers to ensure the successful implementation of the curriculum ; however, the lived experiences of teachers, who were involved primarily in the classroom-based curriculum implementation, were not given further attention. A phenomenological study was used to examine the lived experiences of teacher in implementing the MTB-MLE as atransitional curriculum from Hiligaynon as the first language to English as the second language. Moreover, the lived experience of teachers according to their inter-subjective knowledge such as interpretative, intuitive, and dialectic was being investigated through an in-depth interview and its findings were interpreted using thematic analysis. The results of this study generatedfive themes that described the lived experience of teachers : (1) teaching environment under MTB-MLE ; (2) teaching and reading under MTB-MLE ; (3)MTB-MLE facilitator ; (4) lack ofknowledge of the local language and culture ; and (5) challenges in bridging L1 to L2. Thus, the inter-subjective knowledge of teachers reshaped the MTB-MLE because their "lived experience" either complemented or contradicted this curriculum implementation.